Optimizing correction and restoring alignment - Abdullah Ayish; Muhammad Faisal Ejaz; Abdul Haseeb Butt; Zehra Fatima; Waleed Tariq; Muhammad Momin Khan; Muhammad Idrees; Ajay Pandeya (Medicine, 2026)
Thoracolumbar burst fractures are a major cause of spinal morbidity. While long-segment posterior fixation is traditionally used, short-segment fixation augmented with bone substitutes has been proposed to preserve motion segments while maintaining stability. This study aimed to evaluate radiological outcomes, specifically kyphotic angle correction and vertebral body height restoration, following short-segment fixation with bone substitute in patients with unstable thoracolumbar burst fractures. This retrospective descriptive case series was conducted at a tertiary care center in Sindh, Pakistan, from July 2022 to January 2023. Patients aged 16 to 65 years with single-level unstable thoracolumbar burst fractures (Arbeitsgemeinschaft für Osteosynthesefragen type A3/A4) undergoing short-segment posterior fixation with calcium hydroxyapatite augmentation were included. Kyphotic angle and vertebral body height were measured at baseline and at 3 months post-op using standardized methods. Statistical comparisons were performed using paired t -tests, with P < .05 considered significant. A total of 82 patients were analyzed, including 47 males (57.3%) and 35 females (42.7%), with a mean age of 48.4 ± 8.2 years. Fractures were classified as A3 (53.7%) and A4 (46.3%). Mean vertebral body height increased from 48.7 ± 1.2 mm preoperatively to 86.7 ± 3.2 mm postoperatively ( P < .001). Mean kyphotic angle decreased from 20.4 ± 2.3° to 6.7 ± 2.1° ( P < .001). Short-segment posterior fixation with bone substitute was associated with improved vertebral body height and reduction in kyphotic deformity in patients with unstable thoracolumbar burst fractures. Given the descriptive design and absence of a control group, these findings should be interpreted as observational. Further comparative studies with long-term follow-up are required to establish durability and clinical effectiveness.